Olivia counts - Falconer, Ian (Atheneum Books for Young Readers, 2002)
Olivia, the piglet, helps toddlers learn to count from one to ten.
On board pages.
Cover title.
Olivia, the piglet, helps toddlers learn to count from one to ten.
Keywords: Pigs / Fiction.; Number concept in children.; Counting / Juvenile fiction.; Swine / Fiction.